Comprehensive Wealth, Intangible Capital, and Development - Ferreira, Susana; Hamilton, Kirk (2012)
Existing wealth estimates show that in most countries intangible capital is the largest share of total wealth. Intangible capital is calculated as the difference between total wealth and tangible (produced and natural) capital. This paper uses new estimates of total wealth, natural capital, and physical capital for a panel of countries to shed light on the constituents of the intangible capital residual. In a development-accounting framework, the authors show that factors of production are very successful in explaining the variation in output per worker when they use intangible capital instead of human capital as a factor of production. This suggests that intangible capital captures a broad range of assets typically included in the total factor productivity residual. Human capital is an important factor, both in statistical and economic terms, in regressions decomposing intangible capital.